Pendidikan Profetik untuk Anak di Era Digital: Upaya Menangani Kecanduan Gadget pada Anak - Kuswantoro Kuswantoro (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2020)
The more sophisticated growth of this technology causes the features in the gadget to be more varied and attractive. Recently there have been many cases where children are addicted to gadgets and are getting worse. Not only does it make the child not want to be separated from the gadget, it also shows the aggressive behavior of the child when not given permission to use it. Gadgets can provide a positive role for children to be able to access broader information through the internet, but gadgets can also have a negative influence on children when children over-use gadgets, especially when using game applications to excess. The object of this research is various cases of children addicted to gadgets, through case studies with qualitative methods. This research concludes that the use of Google Family is effective for monitoring children in using gadgets. Islam itself views the use of gadgets as something that means that Islam does not forbid the use of gadgets in daily life.